Development of a land stability index for land damage assessment: the case of a nickel mine, North Konawe, Indonesia - Baba Barus; Suria Darma Tarigan; Reni Kusumo Tejo; Yuri Ardhya Stanny (Journal of Degraded and Mining Lands Management, 2022)
Assessment of land damage has been included in several Indonesian government policies, but it tends to have zero dimensions or only one point in the year. This study tried to propose an inter-time assessment of land damage with a land stability index by including the development of knowledge and technology at nickel mining sites in the easternmost part of North Konawe Regency. Orthophoto and Digital Elevation Model (DEM) images from drones in 2020 were taken in a field survey and used as primary data. While the SPOT 5 Imagery in 2014 and National DEM were collected as secondary data. The developed method combining slope, soil, TRI (Terrain Ruggedness Index), and land cover factor has been considered moderately accurate. Applying the method between different periods has produced a temporal land stability index where a positive value means more unstable, zero means unchanged, and a negative value means more stable. The results showed that after six years, the largest area due to nickel mining in the area has not changed much or had zero value. This is because the area tends to remain a natural forest. The more stable area is located in the southern part of the study site. However, the increasingly unstable area is located in the northern part of the study site. If no reclamation action is taken, the potential for further damage will occur.